ANALISIS KINERJA KOPERASI UNIT DESA (KUD) MINA TELUK SEMANGKA DI KABUPATEN TANGGAMUS PROVINSI LAMPUNG BERDASARKAN PENDEKATAN TRIPARTITE - Saputri, Dita Nastiti; Lestari, Dyah Aring Hepiana; Sayekti, Wuryaningsih Dwi (Lampung University, 2019)
This research aims to analyze cooperative’s performance as business entities, cooperative’s contribution towards development, the economic advantage of cooperative for members, and the non economic advantages (satisfaction) of cooperative for members. This research was conducted purposively at KUD Mina Teluk Semangka in Tanggamus District Lampung Province by a case study method. Total respondents were 51 members of the cooperative taken by simple random sampling, consisted of fishermen, fish trader and fish processor. The research data was analyzed by quantitative descriptive analysis, customer satisfaction index analysis and importance performance analysis. The results of this research showed that business entities performance of KUD Mina Teluk Semangka included into qualified category. KUD Mina Teluk Semangka has contributed towards the development in good category, based on the obedient of cooperation to pay taxes and the average ratio of labor absorption. The economic advantage for members was received by the service cost of selling and purchasing. Total average economic advantages of cooperative’s members per year were Rp922,613.00 for fishermen, Rp386,000.00 for fish trader and Rp394,400.00 for fish processor. The non economic advantages (satisfaction) for members upon service performance and fulfillment of member’s needs was in high category. Key words: KUD, performance, satisfaction, tripartite